Analysis Of Demand Forecasting For Top Sales Products During The Month Of Ramadan In The Frozen Dairy Category Using The Single Exponential Smoothing (SES), Single Moving Average (SMA), And Double Moving Average (DMA) Methods - Hanun Hakim Wibowo; Anjar Priyono (Cita konsultindo, 2026)
Demand patterns tend to change when entering seasonal periods such as Ramadan, so accurate demand forecasting is needed to ensure that the supply chain runs optimally. Hypermart Pakuwon Mall Yogyakarta experienced out of stock and overstock for several of its products at the start of Ramadan, indicating that more accurate forecasting results are needed to prevent this from happening again. This study aims to find the best demand forecasting method for Hypermart Pakuwon Mall Yogyakarta. This study compares demand forecasting methods for top-selling dairy frozen products during Ramadan using the Single Exponential Smoothing (SES), Single Moving Average (SMA), and Double Moving Average (DMA) methods. The forecasting results of each method are then measured using Mean Absolute Percentage Error (MAPE). If a forecasting method produces the smallest MAPE value, it can be said to be the best forecasting method. The results show that the Double Moving Average Order 12 method has the smallest MAPE value of 17.36%. In this case, the Double Moving Average Order 12 method is the best 2 method to use for forecasting com